Prevalencia de lesiones cervicales no cariosas en pacientes adultos que acudieron al servicio Odontológico de la clínica UAN, sede Armenia en 2018-2019 (2020)
During the 1st and 2nd period of 2018, and respectively the 1st and 2nd of 2019 was carried out a descriptive, observational-retrospective study was with adult patients who attended the dental service at Universidad UAN, Armenia headquarter, to determine and the prevalence of LCNC non-carious cervical lesions and possible associations with other etiological triggers, such as bruxism, type of occlusion, dental absences, type of arc, Stacking, etc., This observation and analysis was carried out in the relevant annotations, found in the Clinical Records processed and correctly supported during the periods mentioned above. The results were analyzed afterwards using Excel, an application software that works with spreadsheets. This is part of the Microsoft office package. Therefore, the use of this software for data analysis was convenient. Recording that the prevalence of LCNC is of 37.56% on the total population, being the abfraction the most incident with 18.90%, the LCNC restored with 11.72%, the abrasion with 3.59% and the erosion with 3.35%. Age group 3, that is, patients between 46 and 65 years of age, report these lesions more in the vestibular area, with higher prevalence in men, with no statistically significant difference p:>0,05 from women. The most affected quadrants are quadrants III and IV, with the group of posterior teeth having the greatest condition.